2022
DOI: 10.1186/s12888-022-03690-z
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Factors associated with insomnia among frontline nurses during COVID-19: a cross-sectional survey study

Abstract: Background Research predominantly suggests that nurses are at high risk of developing psychopathology. The empirical data show that the occurrence rate of problem-related sleep quality among clinical nurses is high. Therefore, this study was conducted to address the lack of information on the relationship between the coronavirus disease 2019 (COVID-19) pandemic and insomnia. Methods A convenience sample of nurses (n = 680) completed an online surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 78 publications
1
10
0
4
Order By: Relevance
“…The present study also found some sex differences. In line with numerous studies, females reported a higher fear of COVID-19 than males in the present study (Fullana et al, 2020 ; Nazari et al, 2022 ). Being older was associated with a higher outlook, greater resilience, increased healthy emotionality, and less fear of COVID-19.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study also found some sex differences. In line with numerous studies, females reported a higher fear of COVID-19 than males in the present study (Fullana et al, 2020 ; Nazari et al, 2022 ). Being older was associated with a higher outlook, greater resilience, increased healthy emotionality, and less fear of COVID-19.…”
Section: Discussionsupporting
confidence: 93%
“…Neuroticism is a key trait associated with most emotional disorders (Brown & Barlow, 2009 ). COVID-19 studies describing the etiological role of neuroticism in psychopathology have proposed similar mediators, such as loneliness (Gubler et al, 2020 ) and emotional dysregulation (Nazari et al, 2022 ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies have uncovered a high prevalence of insufficient sleep (70.1%), insomnia (36.0%), and self-reported short sleep duration (≤6 h) (48.6%) among nurses working shifts [ 15 ], as well as frequent reports of poor sleep quality (78%) [ 16 ]. Recent studies conducted during the pandemic show a similar high prevalence of sleep disturbances [ 17 ] and insomnia symptoms [ 18 , 19 , 20 ] among healthcare workers. Furthermore, a recent study from Norway utilizing the same data as in the present study found that the majority of nurses reported no change in sleep duration (84.2%), sleep quality (82.4%), or sleep patterns from before to during the pandemic (data collected between the first and the second pandemic wave) compared to retrospective accounts of their sleep before the pandemic [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current pandemic has generated frequent and intense negative emotions[ 9 ]. Research indicates that psychiatric comorbidities or multiple co-occurring mental health problems are highly prevalent during the pandemic[ 10 , 11 ]. Traditional treatments or specific disorder protocols that target one diagnosis at a time ( e.g.…”
Section: Introductionmentioning
confidence: 99%